2021
DOI: 10.1007/978-3-030-65768-0_8
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity Metabolism of Renal Cell Carcinomas

Abstract: According to data from the American Cancer Society, cancer is one of the deadliest health problems globally. Annually, renal cell carcinoma (RCC) causes more than 100,000 deaths worldwide [1–4], posing an urgent need to develop effective treatments to increase patient survival outcomes. New therapies are expected to address a major factor contributing to cancer’s resistance to standard therapies: oncogenic heterogeneity. Gene expression can vary tremendously among different types of cancers, different patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Examination of different tumor types revealed that the balance between aerobic glycolysis and oxidative phosphorylation could be very different. In a study evaluating the variability of metabolic gene expression across multiple different tumor types, it was found that there was an upregulation of genes related to oxidative phosphorylation in ovarian, lymphoma [27], leukemia, and lung cancers, whereas the opposite was true in thyroid, colon, pancreatic [28], and renal cancers [29,30]. It is thought that the variable activation of different oncogenes such as RAS, AKT, and c-MYC is the driver behind these differences [31][32][33][34][35].…”
Section: Heterogeneity In Glucose Metabolismmentioning
confidence: 99%
“…Examination of different tumor types revealed that the balance between aerobic glycolysis and oxidative phosphorylation could be very different. In a study evaluating the variability of metabolic gene expression across multiple different tumor types, it was found that there was an upregulation of genes related to oxidative phosphorylation in ovarian, lymphoma [27], leukemia, and lung cancers, whereas the opposite was true in thyroid, colon, pancreatic [28], and renal cancers [29,30]. It is thought that the variable activation of different oncogenes such as RAS, AKT, and c-MYC is the driver behind these differences [31][32][33][34][35].…”
Section: Heterogeneity In Glucose Metabolismmentioning
confidence: 99%
“…It was reported that SM accumulate in the HCT-116 (human colon cancer cell lines) during apoptosis [44]. Hence, their overall downregulation might be related to the regulation of cancer cell survival [45].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gameiro et al found that the transcription factor HIF expression maintained a low level of intracellular citrate to maintain adequate lipogenesis. Therefore, the von Hippel-Lindau (VHL)deficient RCC cells that constitutively express HIF-1α and/or HIF-2α become heavily dependent on glutamine for proliferation [26,27].…”
Section: Glutamine Addictionmentioning
confidence: 99%